Being and Hearing Making Intelligible Worlds in Deaf Kathmandu - Graif, Peter (Malinowski Monographs, 2018)
"How do deaf people in different societies perceive and conceive the world around them? Drawing on three years of anthropological fieldwork in Nepali deaf communities, Being and Hearing shows how questions of cultural difference are profoundly shaped by local habits of perception. Beginning with the premise that philosophy and cultural intuition are separated only by genre and pedigree, Peter Graif argues that Nepali deaf communities-in their social sensibilities, political projects, and aesthetics of expression-present innovative answers to the very old question of what it means to be different. From pranks and protests, to diverse acts of love and resistance, to renewed distinctions between material and immaterial, deaf communities in Nepal have crafted ways to foreground the habits of perception that shape both their own experiences and how they are experienced by the hearing people around them.